2008
DOI: 10.17796/jcpd.32.3.j22m7t8163739820
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Liquid Medicaments – Do They Erode The Teeth Surface? An In Vitro Study: Part I

Abstract: The present study was conducted to investigate the endogenous erosive potential of some of the most commonly used pediatric liquid medicaments in our day to day practice. Eight commonly used pediatric liquid medicaments were selected and their endogenous pH was measured using a pH electrode meter. Twenty four exfoliated or extracted primary teeth without any carious lesion/restorations, maintained in selected pediatric liquid medicaments were observed under SEM after 1 min, 10 mins and 8 hours of time interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
16
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 12 publications
5
16
0
2
Order By: Relevance
“…Evidence from in-vitro studies have established that acidic medicines reduced enamel hardness in deciduous teeth [12] with morphological surface alterations of enamel [13] and restorative materials [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from in-vitro studies have established that acidic medicines reduced enamel hardness in deciduous teeth [12] with morphological surface alterations of enamel [13] and restorative materials [14].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been done in the US [4], Brazil [2], New Zealand [3], and Saudi Arabia [23] linking frequent use of sweetened LOM and the development of dental caries. Other authors studied the pH and concentration of sugars of pediatric liquid medicaments and suggested that these medications can pose as a threat to dental health [5,13]. However, only half of the overall medicines that showed sugar in their ingredients presented this information in their directions [24].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the usage of these formulations in a short period may also be considered as prolonged outcomes [15, 21]. Their sugar containing properties might result in erosive and/or cariogenic potentials on teeth surfaces because of increased acidity [15, 1723].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, previous in vitro studies have also shown that acidic medicines could reduce deciduous enamel hardness [13, 16] and cause morphological enamel surface alterations [18] and surface degradation of restorative materials [20]. Other concerning factors with regard to dental caries and dental erosion are the high viscosity of liquid oral medication [9, 21], lack of oral hygiene after medicine’s intake [21] and its frequency of intake, especially in children that present chronic diseases and need to make regular use of liquid oral medicines [3, 9]…”
Section: Introductionmentioning
confidence: 99%